Nurses' negative affective states, moral disengagement, and knowledge hiding: The moderating role of ethical leadership. (5th October 2018) - Zhao, Hongdan; Xia, Qing
Abstract: Aim: This study aims to investigate the influence of nurses' negative affective states on their knowledge‐hiding behaviours through moral disengagement, and especially the moderating role of ethical leadership. Background: Researchers have paid much attention to the harmfulness of knowledge hiding, yet the mechanisms of why and how nurses' negative affective states have an impact on their knowledge‐hiding behaviours are less clear. Method: Two different questionnaire surveys were used in two different studies. In Study 1, a research design with three stages, including 323 nurses (64.47% response rate, 51.70% male) working in a hospital in Shanghai, China, was used. Study 2 involved 317 nurses (63.40% response rate, 51.74% male) working in five hospitals in Shanghai, China. The two studies shared the same statistical method, in which hierarchical regression analyses, the Sobel test, and bootstrap estimates were used to test hypotheses. Results: We found that (a) nurses' negative affective states were positively related to their knowledge‐hiding behaviours; (b) moral disengagement partially mediated this relationship in Study 1, but fully mediated it in Study 2; and (c) ethical leadership mitigated the indirect relationship between negative affective states and knowledge hiding via moral disengagement. Conclusion: Nurses with negative affective states are more likely to activate moral disengagement as a secondary cognitive process to make personal moral rules momentarily obscure, which, in turn, leads them to hide knowledge that is requested by other members. The above relationships will depend on the levels of ethical leadership. Implications for Nursing Management: Nurse managers should try to reduce nurses' knowledge‐hiding behaviours by addressing nurses' negative affective states, decreasing nurses' moral disengagement, and performing ethical leadership behaviours.